Shadow Economies around the World: What do we really know? - Friedrich G. Schneider (Institut für Angewandte Wirtschaftsforschung (IAW), 2004)
Using the DYMIMIC approach, estimates of the shadow economy in 110 developing, transition and developed OECD countries are presented. The average size of the shadow economy (in percent of official GDP) over 1999-2000 in developing countries is 41%, in transition countries 38% and in OECD countries 17%. An increasing burden of taxation and social security contributions are the driving forces of the shadow economy. If the shadow economy increases by one percent the growth rate of the ?official? GDP of a developing (of a developed and/or transition) country decreases by 0.6% (increases by 0.8 and 1.0% respectively).
Keywords: H11; H2; H26; D78; O5; O17; 330; shadow economy; interaction of the shadow economy with the official one; tax burden; government regulation; DYMIMIC method; Schattenwirtschaft; Steuerbelastung; Wirtschaftswachstum; Schätzung; Welt; Entwicklungsländer; Osteuropa; OECD-Staaten